Consumption of differently processed milk products and the risk of asthma in children - Koivusaari Katariina; Syrjälä Essi; Niinistö Sari; Ahonen Suvi; Åkerlund Mari; Korhonen Tuuli E.; Toppari Jorma; Ilonen Jorma; Kaila Minna; Knip Mikael; Alatossava Tapani; Veijola Riitta; et al. (WILEY, 2022)
Background Consumption of unprocessed cow's milk has been associated with a lower risk of childhood asthma and/or atopy. Not much is known about differently processed milk products. We aimed to study the association between the consumption of differently processed milk products and asthma risk in a Finnish birth cohort. Methods We included 3053 children from the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Nutrition Study. Asthma and its subtypes were assessed at the age of 5 years, and food consumption by food records, at the age of 3 and 6 months and 1, 2, 3, 4, and 5 years. We used conventional and processing (heat treatment and homogenization)-based classifications for milk products. The data were analyzed using a joint model for longitudinal and time-to-event data. Results At the age of 5 years, 184 (6.0%) children had asthma, of whom 101 (54.9%) were atopic, 75 (40.8%) were nonatopic, and eight (4.3%) could not be categorized. Consumption of infant formulas [adjusted hazard ratio (95% confidence intervals) 1.15 (1.07, 1.23), p < .001] and strongly heat-treated milk products [1.06 (1.01, 1.10), p = .01] was associated with the risk of all asthma. Consumption of all cow's milk products [1.09 (1.03, 1.15), p = .003], nonfermented milk products [1.08 (1.02, 1.14), p = .008], infant formulas [1.23 (1.13, 1.34), p < .001], and strongly heat-treated milk products [1.08 (1.02, 1.15), p = .006] was associated with nonatopic asthma risk. All these associations remained statistically significant after multiple testing correction. Conclusions High consumption of infant formula and other strongly heat-treated milk products may be associated with the development of asthma.